Decision Support System for Raskin Recipients Recommendation Using Simple Multi Attribute Rating Technique Exploiting Ranks Method - Pandi Barita Nauli Simangunsong (Jurnal Mantik, 2020)
City parks are the main resource in improving the quality of the environment, therefore a good and quality city park is needed to improve the quality and quality of health. One of the efforts to get a quality and good park location is to choose the location of the opening of the park properly. The decision support system carried out at the Medan City Park Service is still conventional which is only based on certain elements so that the assessment is still subjective. Based on these problems, in this study a decision support system was developed using the Analytical Hierarchy Process (AHP) method for determining the location of urban park development. This system uses user-defined criteria and intensity, processed with AHP calculations, and produce a list of assessments for each city park location that will be selected. The results of testing this decision support system state that the system has been running correctly, so this system can be used to assist leaders in making more objective decisions on choosing the location of city parks.